2010
DOI: 10.1186/1759-2208-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Is the transition from chemistry to biology a mystery?

Abstract: Today most chemists think that the answer to how life on earth emerged is still unknown. They assume a gap between chemistry and biology that is still unbridged. For chemists, understanding the origin of life requires the experimental modeling of a process that bridges this gap. They will not consider the problem solved before they are able to perform such tasks. No gap appears when we are pursuing a less ambitious goal, namely, to present a sequence of hypothetical processes that lead to an apparatus with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Theories from quite different domains such as, to name a few, probability theory [7][8][9][10], information theory and the emergence of complex systems [11][12][13][14][15][16][17][18], quantum relativity/cosmology [19][20][21][22][23][24][25][26][27][28][29] and string theory [30] operate with entropy and the Second Law of thermodynamics yet in conjunction with parameters different from the ones studied here. Urgent problems are being at least attacked, and possibly solved, through the insight into apparent and/or fundamental analogies between statistical thermodynamics and, for example (respectively), randomness of sequential irregularities ("algorithmic entropy", "approximate entropy"), computational compactness ("logical depth"), quality change of hereditary information (change in systemic "knowledge" through periodically discarded "Shannon entropy"), the dynamics of black holes ("Bekenstein-Hawking entropy"), and tracing back the microscopic origin of their area-entropy by counting the degeneracy of periodic and persistent topological defects (Bogomol'nyiPrasad-Sommerfield soliton bound states) in certain kinds of supersymmetric branes that mimic the thermodynamics of idealised extremal, highly charged black holes.…”
Section: Resultsmentioning
confidence: 99%
“…Theories from quite different domains such as, to name a few, probability theory [7][8][9][10], information theory and the emergence of complex systems [11][12][13][14][15][16][17][18], quantum relativity/cosmology [19][20][21][22][23][24][25][26][27][28][29] and string theory [30] operate with entropy and the Second Law of thermodynamics yet in conjunction with parameters different from the ones studied here. Urgent problems are being at least attacked, and possibly solved, through the insight into apparent and/or fundamental analogies between statistical thermodynamics and, for example (respectively), randomness of sequential irregularities ("algorithmic entropy", "approximate entropy"), computational compactness ("logical depth"), quality change of hereditary information (change in systemic "knowledge" through periodically discarded "Shannon entropy"), the dynamics of black holes ("Bekenstein-Hawking entropy"), and tracing back the microscopic origin of their area-entropy by counting the degeneracy of periodic and persistent topological defects (Bogomol'nyiPrasad-Sommerfield soliton bound states) in certain kinds of supersymmetric branes that mimic the thermodynamics of idealised extremal, highly charged black holes.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with this conception, test experiments demonstrated that the conformation of the photosensitive molecule can be switched by irradiation with visible and ultraviolet light, as was expected. [1] With the help of scanning tunneling microscopy data of molecular resolution, the authors demonstrate that the TATA molecules form a well-defined network on the clean Au(111) gold substrate. Formation of such two-dimensional, supramolecular structures on solid surfaces by adsorption of suitable organic ligands is a highly interesting topic that met with considerable attention recently.…”
Section: Remote Control Of Interface Propertiesmentioning
confidence: 98%
“…When considering implications for life science, it is worthwhile to mention the ongoing discussion about the origin of life (see for example, the recent paper by Kuhn [1] ). In some of the theoretical models put forward, chemical processes at surfaces have been proposed to play a crucial role.…”
Section: Introductionmentioning
confidence: 99%
“…Chang [ 17 ], Oró [ 18 ], Lazcano [ 19 ], Pace [ 20 ], Eschenmoser & Loewenthal [ 21 ], Orgel [ 22 ], Bada [ 23 ], Snooks [ 24 ], Root-Bernstein [ 25 ] and many others reviewed the chemical and biological constraints on life’s origin on Earth, including the inherent philosophical implications. Kuhn [ 26 ], Pross [ 27 , 28 ], Pascal & Pross [ 29 ], and Luisi [ 30 ] among others, highlighted the problems of understanding the transition from chemical to biological processes and the abiotic synthesis of biomolecules. The goal now is to understand, perhaps from experimental reproduction [ 31 ], the formation of a chemical system that is self-sustained, kinetically stable, dynamically evolvable, and far from thermodynamic equilibrium, which we then could call “alive” or “animate”.…”
Section: Geochemical and Historical Contextsmentioning
confidence: 99%